PENINGKATAN KEMAMPUAN KETERAMPILAN MENULIS TEKS PROSEDUR MELALUI MEDIA VIDEO TIKTOK SISWA KELAS XI.11 SMA NEGERI 5 PALEMBANG - Sari Ulfa Umami; Ayu Sugiarti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Umami, Sari Ulfa and Sugiarti, Ayu 2024. Improving Procedural Text Writing Skills Through Tiktok Video Media for Class XI Students of SMA Negeri 5 Palembang. Classroom Action Research Report, Indonesian Language Education Study Program, Pre-Service Teacher Professional Education Program (PPG), Faculty of Teacher Training and Education, PGRI University, Palembang. Lecturer in the Classroom Action Research course Hetilaniar, M.Pd.